Role of NRF2 in Ovarian Cancer - Giovanni Tossetta; Sonia Fantone; Eva Montanari; Daniela Marzioni; Gaia Goteri (MDPI AG, 2022)
Among gynaecologic malignancies, ovarian cancer is one of the most dangerous, with a high fatality rate and relapse due to the occurrence of chemoresistance. Many researchers demonstrated that oxidative stress is involved in tumour occurrence, growth and development. Nuclear factor erythroid 2-related factor 2 (NRF2) is an important transcription factor, playing an important role in protecting against oxidative damage. Increased levels of Reactive Oxygen Species (ROS) activate NRF2 signalling, inducing the expression of antioxidant enzymes, such as haem oxygenase (HO-1), catalase (CAT), glutathione peroxidase (GPx) and superoxide dismutase (SOD), that protect cells against oxidative stress. However, NRF2 activation in cancer cells is responsible for the development of chemoresistance, inactivating drug-mediated oxidative stress that normally leads to cancer cells' death. In this review, we report evidence from the literature describing the effect of NRF2 on ovarian cancer, with a focus on its function in drug resistance, NRF2 natural and synthetic modulators and its protective function in normal ovarian preservation.